Spectroscopic studies of erbium doped zinc tellurite glass embedded with gold nanoparticles [electronic resource] - Erna Jaafar, author; Md. Rahim Sahar, supervisor; Sib Krishna Ghoshal, supervisor; Fakulti Sains (2014)
Thesis (Sarjana Sains (Fizik)) - Universiti Teknologi Malaysia, 2014